Rancangan Pembuatan Game Edukasi Bahasa Indonesia Menggunakan Npc (Non Player Character) - R. Fahendra Hadi S (Informatics Engineering Department-UWKS, 2019)
In this pandemic era, many schools are implementing online learning. Most students cannot understand the material from the teacher given, so students are not interested in online learning activities. Therefore, the author designed an Indonesian language educational game, so that students have an interest in the edugame application. Edugames are effective enough to convey a material or teaching materials, as well as provide a different user experience than the conventional learning process. From the description above, the author asserts that the application of artificial intelligence elements into educational games will increase user interest in educational games themselves. So this study aims to analyze the assessment or input from users on the development of educational games that use Non-Player Character (NPC)[1]. In addition, the built NPC also applies the Natural Language Processing (NLP) method so that it can answer questions automatically.